K-Regular Domination In Hesitancy Fuzzy Graph - S.K.Sriram Kalyan (International Journal of Modern Agriculture, 2021)
In this paper we define regular domination set and regular dominating number in hesitancy fuzzy graph and investigate some properties and bounds of regular domination number in varioushesitancy fuzzy graphs.